2019
DOI: 10.3390/jof5010018
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pulmonary Aspergillosis in Patients with Underlying Respiratory Disorders in Cuba—A Pilot Study

Abstract: Chronic pulmonary aspergillosis (CPA) is a fungal infection with high mortality and morbidity rates. This disease is caused by several Aspergillus species and affects patients with an underlying respiratory condition. This pilot study aims to recognize CPA among patients with different respiratory diseases. Twenty-one out of 47 patients were classified as CPA based on the examination of clinical signs and symptoms, radiological findings, mycological culture of respiratory samples and analysis of Aspergillus Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Other commonly used serological assays are primarily specific for A. fumigatus and do not exhibit Aspergillus species cross-reactivity (38, 39) or have not been evaluated for their utility in diagnosing CPA caused by non-A. fumigatus strains (22, 40).…”
Section: Discussionmentioning
confidence: 99%
“…Other commonly used serological assays are primarily specific for A. fumigatus and do not exhibit Aspergillus species cross-reactivity (38, 39) or have not been evaluated for their utility in diagnosing CPA caused by non-A. fumigatus strains (22, 40).…”
Section: Discussionmentioning
confidence: 99%
“…The specimens’ investigation was done as per the manufacture’s recommendations with an optical density (OD) cut-off of 1 for a positive IgG serum level. Moreover, we analyzed with the cut-off OD value of 0.9 to find differences between the IgG serum levels [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies conducted in high TB burden settings such as India and Uganda evaluating CPA in post-TB patients estimated CPA to be more common in cavitary disease [9,10]. Another study from Cuba also showed an association between high levels of Aspergillus immunoglobulin G (IgG) and the presence of cavities [11]. If left untreated, CPA is associated with significant morbidity and mortality [3][4][5].…”
Section: Introductionmentioning
confidence: 99%